Rietveld analysys and electrical properties of lanthanum doped BiFeO3 ceramics - Simões, Alexandre Zirpoli [UNESP]; Garcia, Filiberto Gonzalez; Riccardi, Carla dos Santos [UNESP] (Elsevier B.V. Sa, 2009)
Lanthanum-modified bismuth ferrite ceramics, Bi1-xLaxFeO3 (BLFO), with x ranging from 0 to 0.30 were obtained using a polymeric precursor solution. Orthorhombicity of the system raised with the increase of lanthanum content in the BFO crystal lattice. No secondary phases were evident after lanthanum addition. This study underlines the role of the preparation route on the structural and morphological characteristic of the obtained materials and their influence on the electrical behavior. A homogeneous size distribution of BFO powders was evidenced by scanning electron microscopy. Increasing lanthanum content leads to lower leakage current density and superior ferroelectric hysteresis loops at room temperature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Annealing; Rietveld analyses; Ferroelectricity